2022
DOI: 10.3390/molecules27030584
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics (Polystyrene) Exposure Induces Metabolic Changes in the Liver of Rare Minnow (Gobiocypris rarus)

Abstract: Microplastics are environmental contaminants and an emergent concern. Microplastics are abundant in freshwater and can cause biochemical stress in freshwater organisms. In the current study, rare minnows (Gobiocypris rarus) were exposed to 1μm polystyrene microplastics at 200 μg/L concentration. We observed various sublethal effects after four weeks of exposure but no mortality. Numerous cellular and tissue alterations were observed in the liver. Differential metabolites and differentially expressed genes betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The toxic effects of MPs on the liver are receiving more attention from researchers. Currently, the research on the toxic effects of MPs/NPs on the liver mainly focuses on marine fish [ 69 , 124 ]. Since the pollution of MPs in the ocean is not optimistic, and fish are the main marine species that people eat, it is crucial to study the impact of MPs on marine fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxic effects of MPs on the liver are receiving more attention from researchers. Currently, the research on the toxic effects of MPs/NPs on the liver mainly focuses on marine fish [ 69 , 124 ]. Since the pollution of MPs in the ocean is not optimistic, and fish are the main marine species that people eat, it is crucial to study the impact of MPs on marine fish.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in MPs-exposed fish, MPs exposure also perturbed the metabolomic profile in the fish liver, with alterations in the metabolites mainly involving carbohydrates, fatty acids, amino acids, and nucleic acids. MPs exposure can also cause significant changes in most monosaccharide metabolic pathways, including galactose metabolism, fructose and mannose metabolism, pentose phosphate pathway, pentose and glucuronic acid interconversion, and glycolysis/gluconeogenesis [ 124 ].…”
Section: Potential Mechanisms Of Mps/nps Toxicity On the Livermentioning
confidence: 99%
“…Since MPs/NPs can cause mitochondrial damage, it is expected that NPs interfere with the ability to produce ATPs and mobilize energy reserve, which is further echoed by liver and serum metabolite analyses related to tricarboxylic acid cycle and glycolysis[ 23 , 24 ]. Moreover, liver transcriptomic and metabolomic studies revealed MPs/NPs can perturb monosaccharide and lipid metabolism including pentose phosphate pathways and gluconeogenesis[ 25 , 26 ]. Not only do MPs/NPs inhibit building block synthesis and signal transduction, but they also damage intestinal function and suppress the absorption of nutrients[ 27 ].…”
Section: Hepatocyte Energy Deprivationmentioning
confidence: 99%
“…For example, in fish, MNPs lead to formation of reactive oxygen species (ROS) and increased oxidative stress, inducing cellular damage in liver, blood cells, gills, digestive tract, and brain (Pitt et al, 2018b;Hu and Palic, 2020;Buwono et al, 2022;Capóet al, 2022;Hoyo-Alvarez et al, 2022;Rangasamy et al, 2022). In fish, MNPs induced mitochondrial stress, altered hormonal regulation of energy metabolism, and catabolic and anabolic processes, which can limit the ability and flexibility of the organism to respond to future stresses (Brun et al, 2019;Trevisan et al, 2019;Trevisan et al, 2020;Wang et al, 2022). Such alterations affect animal fitness, reproduction, and success (Dreier et al, 2019).…”
Section: Effects Of Plastics On Animal Healthmentioning
confidence: 99%